2019
DOI: 10.2351/1.5096111
|View full text |Cite
|
Sign up to set email alerts
|

Laser enhancement of wire arc additive manufacturing

Abstract: Additive manufacturing (AM) can be used for the fabrication of large metal parts, e.g., aerospace/space applications. Wire arc additive manufacturing (WAAM) can be a suitable process for this due to its high deposition rates and relatively low equipment and operation costs. In WAAM, an electrical arc is used as a heat source and the material is supplied in the form of a metal wire. A known disadvantage of the process is the comparably low dimensional accuracy. This is usually compensated by generating larger s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…They have acquired an average hardness rating of 355 ± 28 HV0.5 in constructed conditions. The effects of laser amplification with both a leading and the following laser beam on CMT-based WAAM have been researched by Nasstrom et al 81 The topological capabilities of WAAM are found to be best enhanced by a trailing laser beam.…”
Section: High-energy Density (Hed) Welding-based Additive Manufacturingmentioning
confidence: 99%
“…They have acquired an average hardness rating of 355 ± 28 HV0.5 in constructed conditions. The effects of laser amplification with both a leading and the following laser beam on CMT-based WAAM have been researched by Nasstrom et al 81 The topological capabilities of WAAM are found to be best enhanced by a trailing laser beam.…”
Section: High-energy Density (Hed) Welding-based Additive Manufacturingmentioning
confidence: 99%
“…For example, changing the surface energy of the molten pool makes it difficult for droplets to spread. The droplet has a large wetting angle owing to the laser effect (Singh et al , 2022; Näsström et al , 2019; Singh et al , 2021; Chi et al , 2020), as shown in Figure 7. The outcome of using oscillating laser-assisted WAAM is the opposite; herein, the temperature distribution inside the molten pool is altered, which triggers an increase in the width of the deposited layer owing to the impact of the liquid metal from the bottom to the walls of the molten pool (Gong et al , 2020).…”
Section: Changed Molten Pool Dynamicsmentioning
confidence: 99%
“…The primary techniques for aluminum alloy additive manufacturing include la additive manufacturing (LAM) and wire arc additive manufacturing (WAAM) [13-1 LAM offers high forming accuracy but suffers from low production efficiency and exc sive laser energy loss [16,17]. In contrast, WAAM exhibits high productivity but faces ch lenges such as poor forming accuracy and numerous defects [18][19][20]. Combining the vantages of both techniques, laser-arc hybrid additive manufacturing (LAHAM) in grates a laser and an electric arc.…”
Section: Introductionmentioning
confidence: 99%